Análise quantitativa dos tecidos gengivais de ratos tratados com fenitoína e ciclosporina - Spolidório, Luis Carlos [UNESP]; GONZAGA, Heron Fernando de Souza [UNESP]; SPOLIDORIO, Denise M. P. [UNESP] (Sociedade Brasileira de Pesquisa Odontológica e Faculdade de Odontologia da Universidade de São Paulo, 2000)
Os aumentos gengivais podem ser decorrentes de reações teciduais a estímulos idiopáticos, patológicos e farmacológicos. O objetivo desse trabalho foi avaliar morfometricamente e estereologicamente a ação da fenitoína (Fen) e ciclosporina (CsA) sobre os tecidos gengivais de ratos. Dez ratos receberam, por via intraperitonial, Fen na dose inicial de 2 mg/kg de peso corporal/dia, aumentando 2 mg a cada duas semanas, durante 60 dias. em outros 10 ratos, administraram-se, por via subcutânea, 10mg/kg de peso corporal/dia de CsA, durante o mesmo período do grupo anterior. Os valores morfométricos e estereométricos dos tecidos gengivais dos ratos tratados com CsA foram significativamente maiores quando comparado com os valores dos tecidos gengivais do grupo tratado com Fen. Esses resultados sugerem que a CsA na dose utilizada é mais eficaz no desenvolvimento do aumento gengival em ratos, podendo estar atuando na proliferação de fibroblastos e no desequilíbrio fisiológico da síntese de fibras colágenas.

Reactions to a number of idiopathic, pathological and pharmacological stimuli may result in overgrowth of gingiva, whose mechanisms have not been established yet. The aim of the present work was to evaluate morphometrically and stereologically the effect of phenytoin (PHT) and cyclosporine (Cs) on the gingival tissues of rats. Ten rats received daily IP injection of PHT, 2 mg/kg of body weight/day, which was increased in 2 mg at each two weeks, during 60 days. Ten rats received 10 mg/kg of body weight/day of Cs, subcutaneously, during the same period of the previous group. All rats treated with Cs developed gingival overgrowth, with increased thickness of the epithelium, height and wideness of connective tissues, as well as, increased density of fibroblasts and collagen fibers, when compared with the rats treated with PHT and with the control. These results suggest that Cs, in the used dose, is more efficient in the development of gingival overgrowth in rats. Cs-induced gingival overgrowth is a tissue with an altered composition, characterized by increasing of the density of fibroblasts and by physiologic unbalance of collagen synthesis.
Quantitative analysis of gingival tissues of rats treated with phenytoin and cyclosporine
Keywords: Fibromatose gengival; Fenitoína; Ciclosporina; Fibromatosis; Phenytoin; Cyclosporine